Application of in vivo Laser Scanning Microscopy to Visualise the Penetration of a Fluorescent Dye in Solution and in Liposomes into the Skin after Pre-Treatment with Microneedles - C., Meinke Martina; C., Kruithof Annelieke; M., Bal Suzanne; A., Bouwstra Joke; Jürgen, Lademann (IntechOpen, 2011)
None